2017
DOI: 10.1016/j.actamat.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Application of finite element, phase-field, and CALPHAD-based methods to additive manufacturing of Ni-based superalloys

Abstract: Numerical simulations are used in this work to investigate aspects of microstructure and microseg-regation during rapid solidification of a Ni-based superalloy in a laser powder bed fusion additive manufacturing process. Thermal modeling by finite element analysis simulates the laser melt pool, with surface temperatures in agreement with in situ thermographic measurements on Inconel 625. Geometric and thermal features of the simulated melt pools are extracted and used in subsequent mesoscale simulations. Solid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
182
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 346 publications
(196 citation statements)
references
References 55 publications
12
182
1
1
Order By: Relevance
“…We found that the streaks in the as-built IN625 data have a nominal length in q on the scale of 0.1 Å-1, which translates to a segregated region width of ≈ 6 nm. This result is in good agreement with our CALPHAD-based solidification simulations on as-built AM IN625[33], which show that most of the elemental segregation occurs within several nm from the center of the interdendritic regions.…”
supporting
confidence: 90%
“…We found that the streaks in the as-built IN625 data have a nominal length in q on the scale of 0.1 Å-1, which translates to a segregated region width of ≈ 6 nm. This result is in good agreement with our CALPHAD-based solidification simulations on as-built AM IN625[33], which show that most of the elemental segregation occurs within several nm from the center of the interdendritic regions.…”
supporting
confidence: 90%
“…In wrought form, the mechanical strength is derived primarily from solid solution strengthening via alloying with Cr, Mo, and Nb. Additional strengthening has been reported for certain compositions and conditions via precipitation of the metastable body-centered tetragonal D0 22 Ni 3 Nb c¢¢-phase. [9][10][11] Formation of the orthorhombic D0 a Ni 3 Nb d-phase is also possible in any alloy where precipitation strengthening by c¢¢ is possible, including IN625 [9][10][11] and Inconel 718.…”
Section: Introductionmentioning
confidence: 86%
“…Recent Calphad and phase-field modeling has also suggested significant micro-segregation in IN625 produced using L-PBF AM. [22] Zhang et al did not investigate secondary phases, but investigated the homogenization behavior of the highly micro-segregated solidification microstructure. They reported that a homogenization heat treatment of 30 to 60 minutes at 1423 K (1150°C) was sufficient to relieve the solidification micro-segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the high cooling rates (up to 10 7 °C/s) and multiple re-melting events that occur during the AM build process are likely to produce microstructures that are dramatically different than those observed in conventional materials. Specifically, prominent micro-segregation and/or unexpected phases are present, particularly in components where no post-build thermal processing is performed [57]. …”
Section: 0 Introductionmentioning
confidence: 99%